ARTICLE REVIEW “A CASE REPORT OF BLACK HAIRY TONGUE (MELANOTRICHIA LINGUAE OR LINGUA PILOSA NIGRA)” - Yap, Ivana; Chuan, How Kim; Halim, Susanna (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Black hairy tongue (BHT) is a benign but alarming oral condition characterized by hypertrophy and elongation of the filiform papillae, resulting in a black or brown discoloration of the tongue. This case report presents a 64-year-old male who developed BHT after a 10-day course of ceftriaxone and pantoprazole therapy. The patient had no history of smoking, poor oral hygiene, or systemic disease. Clinical observation revealed black discoloration on the dorsal tongue surface. The temporal association between drug administration and lesion onset, along with improvement after medication discontinuation and oral hygiene reinforcement, suggests a drug-induced etiology. The patient's condition improved following the cessation of pantoprazole and substitution of ceftriaxone with trimethoprim-sulfamethoxazole. Literature review indicates that antibiotics, especially beta-lactams, and proton pump inhibitors may play a role in the pathogenesis of BHT by altering oral microbial flora and inhibiting keratin desquamation. This case highlights the importance of clinician awareness regarding rare adverse drug reactions such as BHT. Prompt identification and management, including discontinuation of offending agents and improvement of oral hygiene, are essential for resolution and prevention of unnecessary diagnostic procedures.